Growth and yield of radish (Raphanus sativus L.) treated with different organic manure on alluvial soil - Santari, Putri Tria; Dewi, Dina Omayani; Hartono (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
The productivity of radish plants can be increased using improved varieties and fertilizing the soil to increase its fertility. Using organic fertilizers can improve soil structure and increase productivity on the land. This study aimed to determine the effect of applying organic fertilizer on the growth and yield of radish on alluvial soil. The study was conducted in July-December 2021, using a randomized block design with five treatments and five replications. The treatments were types of organic fertilizers consisting of control, goat manure, chicken manure, ashes (remaining ash from burning leaves), and cow manure. Each type of organic fertilizer was applied with a dose of 6 tons ha-1. The observation shows that the application of chicken manure significantly improves both the vegetative and the generative variables of radish crops. The results of the farm analysis showed that the use of chicken manure yielded more significant benefits, with R/C values of 2.40 and a B/C ratio of 1.40. Keywords: farm analysis; productivity enhancement; soil fertility